(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Bronchial asthma in children is a chronic condition that significantly diminishes the quality of life for school-aged children, impacting school attendance, academic performance, and overall development. Asthma is the most common respiratory disease in childhood, affecting millions of children globally— for instance, it occurs in 10-15% of children in developed countries, while this percentage may be even higher in developing nations. School nurses play a crucial role in preventing and managing this condition, as they are constantly involved in children’s daily lives, implementing educational, monitoring, and intervention programs. This article provides a detailed evaluation of the effectiveness of programs led by school nurses based on a systematic review of scientific studies conducted from 2023 to 2025. The reviewed studies indicate that nurse interventions reduce asthma symptoms by 20-30%, increase school attendance by 15-25%, and significantly decrease emergency interventions and hospitalizations. Furthermore, nursing education programs enhance children’s self-management skills, such as using inhalers, recognizing symptoms, and controlling environmental factors.